2022
DOI: 10.3390/children9040521
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Association between Body Characteristics and Speed Performance over Twenty-Five Years in Italian Adolescents

Abstract: Background: Physical fitness (PF) is positively related to skeletal and metabolic health, and it had an inverse relation with obesity. Adolescents with obesity have the worst performance in PF and speed-agility (SA) that contributes to an augmented risk to develop pathologies. To the best of our knowledge, many studies analyzed the trends of obesity and SA separately, but there is a lack of data about SA ability trends in adolescents with obesity. We aimed to investigate SA trends in children with obesity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The trends in Slovenia are almost consistent with our study 15 , with speed quality first decreasing and then rebounding. However, studies from some developed countries 6,[38][39][40][41][42] showed different results that speed remained stable in children after 2000, having previously 43 . Our study also found that during the period 2010-2019, the speed of adolescents aged 16-18 years had no significant changes, and some studies also provided some evidence 35,44 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The trends in Slovenia are almost consistent with our study 15 , with speed quality first decreasing and then rebounding. However, studies from some developed countries 6,[38][39][40][41][42] showed different results that speed remained stable in children after 2000, having previously 43 . Our study also found that during the period 2010-2019, the speed of adolescents aged 16-18 years had no significant changes, and some studies also provided some evidence 35,44 .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we found significant differences in speed items between countries, with straight-line dashes (e.g., 30/50/60-m dash) being related to the ability to move quickly; speed-agility (e.g., 10 × 5 m shuttle run) also included the ability to change body position/orientation quickly and accurately in response to stimuli 46 . Three types of speed were selected in Italy, and the results of dashes remained almost constant over the last 30 years, but the shuttle run declined 40 . Therefore, we estimate that the differences in secular trends in speed may be related to the test items, although it is known that speed is highly genetically determined 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite established benefits of regular PA practice [ 18 , 123 ], children with obesity usually have lower levels of PA and physical fitness compared to peers [ 124 , 125 ] due to greater difficulties in performing different motor skills and negative feelings and self-esteem related to PA practice [ 126 , 127 ]. As demonstrated by Yu et al [ 128 ], pediatric subjects with obesity spent 30% less time engaging in PA pursuits and 51% more time in sedentary behaviors during time dedicated to waking activities.…”
Section: Physical Activity Levels In Children and Adolescents With Ob...mentioning
confidence: 99%
“…Furthermore, boys aged 10 and 16 years showed higher rates of being physically unfit (with a small and moderate effect size, respectively) than girls, whereas girls aged 13 showed higher rates of being physically unfit (with a small effect size) than boys. A cohort study conducted by Vandoni et al [ 46 ] on 3923 Italian adolescents aged 11–13 years found that overweight and obese adolescents exhibited a slower 5-meter repeated running speed compared to healthy participants. It is well-known that running speed is a physical ability that is directly associated with good body composition [ 47 ], better school performance [ 45 ], and protection against metabolic syndrome [ 48 ].…”
Section: Discussionmentioning
confidence: 99%